The Dynamics of Productive Waqf Management of Islamic Kingdom Property in Java - rosyid, Ahmad Zaenur; bin Shaharudin, Syarul Azman; Sholihah, Hidayatus; Asmaji, Asmaji (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study discusses the dynamics of the management of the waqf land inherited from the Islamic King of Demak Bintaro, Fatahilah, in the form of 350 ha of productive land managed by the Mosque Welfare Agency (BKM) of Demak Regency for the benefit of the community. This study aims to study the diversity of waqf asset management models and their distribution patterns framed in a productive waqf model in line with the provisions of Law No. 41 of 2004 and Government Regulation (PP) No. 42 of 2006 concerning waqf. This study is classified as qualitative which examines Nāzir's activities in managing waqf according to the perspective of Islamic law. Data were collected through in-depth interviews, direct observation, and historical documents, books and related articles. This study concludes that there is a development of management patterns by Nāzir from traditional to semi-professional dynamic governance. This is implemented through the development of a productive economy for waqf land in the form of land auctions and the construction of shophouses, and lodgings for rent. The results are distributed to several segments such as mosques and Qur'an Education Parks (TPQ), schools and graves, including for the commemoration of the royal family haul, maintenance and operational costs of the mosque, and the tomb of the Demak Sultanate.